2016
DOI: 10.1111/1758-2229.12396
|View full text |Cite
|
Sign up to set email alerts
|

Hyperendemic Campylobacter jejuni in guinea pigs (Cavia porcellus) raised for food in a semi‐rural community of Quito, Ecuador

Abstract: Summary Domestic animals and animal products are the source of pathogenic Campylobacter jejuni and C. coli in industrialized countries, yet little is known about the transmission of these bacteria in developing countries. Guinea pigs (Cavia porcellus) are commonly raised for food in the Andean region of South America, however, limited research has characterized this rodent as a reservoir of zoonotic enteric pathogens. In this study, we examined the prevalence of Campylobacter spp. in 203 fecal samples from dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 29 publications
2
18
0
1
Order By: Relevance
“…The rest of the STs and CCs were randomly distributed in the community (Table 2; also see Table S2 in the supplemental material). Further, guinea pigs were the major reservoir of C. jejuni; 21 isolates of this animal species were analyzed by MLST, and nine novel STs were identified solely in guinea pigs (25).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rest of the STs and CCs were randomly distributed in the community (Table 2; also see Table S2 in the supplemental material). Further, guinea pigs were the major reservoir of C. jejuni; 21 isolates of this animal species were analyzed by MLST, and nine novel STs were identified solely in guinea pigs (25).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, STs of C. jejuni from guinea pigs (the animal with the highest prevalence of C. jejuni) seemed to infect only this animal species (Table 2) (25). Previous MLST analyses have found that some C. jejuni strains may be more adapted to one animal species and less likely to infect humans or other hosts (25,29,30). The association of C. jejuni's STs and CCs with specific animal species seemed to concur with findings previously reported (28,30,31).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a study in Ecuador demonstrated that CC-353, CC-354 and CC-607 were present in C. jejuni isolates from backyard poultry and other domestic animals kept in households (Graham et al, 2016 ). A query in the Campylobacter jejuni/coli PubMSLT database ( PubMLST.org , 2016 ) (Last accessed: 21/07/2016) showed that in Latin America, Brazil, and Uruguay reported Campylobacter MLST profiles from chicken samples.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, holding small backyard for raising poultry flocks and guinea pigs are popular among Ecuadorian people as meat source. High Campylobacter isolation rates have been found among these two types of meat source 23 , 24 .…”
mentioning
confidence: 96%